O mobralense e o domínio do léxico - Navarro Rivas, Carmen (1980)
In the present field research, the communication between men through v e rba l codes was studied and the relationsship between language and thought as well as the world perception' made pos sible by the use of language,be it by the individual or the community were a nalysed. Afterwards the school system was examined, since beeing the responsible for the transmission of a peculiar apprehension ofworldand men, which is characteristic for a given nationality and/or for the maintenance of values and living patterns which identify a given community. The above mentioned analysis shows the importance of the reading learning process as well as of the mass programs of teaching men to read, chiefly in underdevelopped countries as Brazil. With these thoughts as a framework, the present research aimed to investigate the vocabulary of thirtyseven students of MOBRAL (Brazilian Movement of Teaching Adults to Read) in the city of Nova Friburgo, relating this vocabulary to some social variables (place of birth, number of years of living in the given geographical a rea, age, sex and profession), to thematic variables (alimentation, health/disease, profession/occupation, life expectation, life memories, free time use/hobbies) which were choosen after a previous study of life conditions and interests of the individuaIs; the vocabulary was also related to linguistic variables, that is word classification. It was also intended in this exploratory study to observe the extension in which written material of MOBRAL second reading books and class A (Jornal do Brasil) and class C (O Dia and Ultima Hora) newspapers are related to the vocabulary used by MOBRAL students at Nova Friburgo. In order to make possible the study of the individuaIs' vocabulary,fifty interviews were registered following the usual methodology of sociolinguistic studies. The data obtained from these registered interviews were analysed by quantitative methods under application of the SPSS computational programo The study of relationships between and arnong the variables (morphological classification of words, thematic variables, age, sex, profession) led to the elaboration of multivariable contingency tables and consequently allowed a pertinent statistical treatment of data. As a result of data analysis a non-variable incidence of use of nouns and verbs in oral communication was observed. Even though the research methodology aimed to register the available vocabulary during the interviews the incidence of nouns use was not altered due to the fact that the interviewed persons did not mention the name of objects and things as isolated wordsi they always used complete phrases. Based on this conclusion two pedagogical suggestions were made to MOBRAL: the first one is that the learning/teaching process must not give priority to nouns (statical process of language) in prejudice of verbs (dinamic process); the second one concerns the use of sentences in the reading/learning strategy. It must also be observed that the study of relationships between and among variables showed that the alterations of incidence in the use of nouns and verbs are re1ated to thematic matters. Examinating the vocabular varieties used by the per sons interviewed in Nova Friburgo there was found a noun frequency of 11 337i out of these 2222 were different nouns and 1590 were different vocabularies; the results for verbs were 17 604, 2365 and 588 and for adjectives 1980, 660 and 488. This means that the vocabulary used by these MOBRAL students may be different from the vocabulary used in other geographica1 areas or by different social classes living under different conditionsi but the vocabulary of the interviewed per sons is neither limited nor restrict. It is expressing how they understand the world in which they live and what they expect from this world. On account of this, another suggestion to MOBRAL: the words to be taught should not only be selected within the different communities where the alphabetization is to be executed but also be directly related to the everyday needs of the adults and the generator noun should be integrated in complete sentences.